Amniotic fluid index versus maximum vertical pocket measurement in predicting perinatal outcome at 40 weeks or beyond - Noor, Nasreen; Raza, Seema Amjad; Parveen, Shazia; Khalid, Mohammad; Ali, Syed Manazir (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: The aim of this study is to compare the use of amniotic fluid index with maximum vertical pocket for predicting perinatal outcomes. Methods: The present study was a prospective observational study and includes 140 The study include normal antenatal women at gestational age 40 weeks or beyond (by last menstrual period/1st trimester scan) referred from antenatal between 20 to 40 years were enrolled in this study from 2015 to 2017. After Institutional Ethics Committee approval all recruited women was assessed at the 3rd trimester visit for baseline demographic and obstetric data. After taking a detailed history and examination the women were subjected to ultrasonography for Amniotic Fluid index (AFI) and Maximum vertical pocket (MVP). The women were divided into 2 groups based on measurement of AFI and MVP ultrasonologically. The correlation of Amniotic fluid index and Maximum vertical pocket with perinatal outcome were computed for the 2 groups: Group Ia - women having normal AFI and normal MVP; Group Ib - women having decreased AFI and normal MVP. Results: In Group Ia, 31(34.44%) women were induced and in Group Ib 59 (65.56%) women were induced for oligohydramnios. 65 women (72.22%) had normal vaginal delivery versus 25women (27.28%) had undergone LSCS in Group Ia, while in Group Ib, 32 women (64%) versus 18 women (36%) had vaginal delivery and LSCS respectively. Higher rate of LSCS was observed in Group Ib. There was no significant difference in the rate of LSCS for fetal distress between Group Ia and Ib for fetal distress. Conclusions: Amniotic fluid index (AFI) compared with the maximum vertical pocket (MVP) excessively characterizes patients as having oligohydramnios, leading to an increase in obstetric interventions, without any documented improvement in perinatal morbidity and mortality. Thus, authors cannot find any objective reason to favour AFI over MVP.